2014
DOI: 10.4236/aim.2014.49063
|View full text |Cite
|
Sign up to set email alerts
|

Caerulomycin A—An Antifungal Compound Isolated from Marine Actinomycetes

Abstract: Actinomycetes have been prolific sources of novel secondary metabolites with a range of biological activities that may ultimately find application as therapeutic compounds. Hence several drug discovery companies are engaged in isolation of novel bioactive metabolites from these microbial sources. Antibiotics form the major class of such bioactive metabolites and have been widely used for treating infectious diseases. One of the most critical problems in clinical practice is the increase of prevalence of drug r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…It was also higher than the MIC values obtained by Singh et al [16] which stretched from 0.5 µg/mL to 3 µg/mL. Ambavane et al [4] also reported less MIC values ranging from 0.39 µg/mL to 1.56 µg/mL. AZ-NIOFD1 recovered from the Nile River, Egypt [52] had MIC range from 0.0117 mg/mL to 0.03125 mg/mL.…”
Section: Minimum Inhibitory Concentration (Mic) Of the Streptomyces Smentioning
confidence: 81%
“…It was also higher than the MIC values obtained by Singh et al [16] which stretched from 0.5 µg/mL to 3 µg/mL. Ambavane et al [4] also reported less MIC values ranging from 0.39 µg/mL to 1.56 µg/mL. AZ-NIOFD1 recovered from the Nile River, Egypt [52] had MIC range from 0.0117 mg/mL to 0.03125 mg/mL.…”
Section: Minimum Inhibitory Concentration (Mic) Of the Streptomyces Smentioning
confidence: 81%
“…The MICs of Caerulomycin A was in the range of 0.39–1.26 µg/mL. Furthermore, the MIC values obtained for Caerulomycin A against fluconazole resistant C. glabrata were comparable with the MIC values obtained for Amphotericin B [ 87 ]. Pyridones, trichodin A ( 157 ) and pyridoxatin ( 158 ), were extracted from both the mycelia and the culture broth of the marine fungus, Trichoderma sp.…”
Section: Miscellaneous Compoundsmentioning
confidence: 82%
“…The number of antifungal agents available for controlling fungal infections is still limited in comparison to antibacterial agents, and their use is still risky owing to toxicity and side effects [28]. Therefore, studies are still being conducted to isolate and identify novel antifungals that are potentially effective against pathogenic fungi [23].…”
Section: Antifungalmentioning
confidence: 99%